GLOBAL TRENDS ON RESEARCH TOWARDS THE VALUATION PROCESS OF AN AGRICULTURE LAND - Silvia CHIOREAN; Iulia COROIAN; Tudor SĂLĂGEAN; Mircea Emil NAP; Jutka DEAK; Ioan LUPUȚ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The increased use of data analytics and machine learning algorithms enables better prediction of land values based on various factors such as soil quality, climate, and historical performance by processing large datasets. The primary objective of this paper is to underscore the significance of addressing the topic concerning the evaluation process of agricultural land. Concurrently, it seeks to accentuate the interconnectedness across various domains of study, encompassing strategic management, agronomy, ecology, agricultural practices, and agricultural policies. Advanced technologies such as satellite imagery, remote sensing, and Geographic Information System (GIS) tools are being integrated for more accurate and efficient land valuation. In the present study, a retrospective and descriptive bibliometric analysis using the Web of Science platform was conducted, identifying ,630 papers on the "valuation of agricultural land" from the year 2000 to 2023, which were then analyzed with VOSviewer and Microsoft Excel to generate visual representations of keyword frequency over time. The paper reveals a notable increase in published articles, emphasizing their relevance due to their economic and financial impact, with a focus on environmental sciences and economics, confirming the topic's importance and its association with ecosystem services, land use change, and willingness to pay. The results demonstrate that this theme is increasingly addressed by researchers.